2012
DOI: 10.1002/cphc.201100779
|View full text |Cite
|
Sign up to set email alerts
|

Glycine in 1‐Butyl‐3‐Methylimidazolium Acetate and Trifluoroacetate Ionic Liquids: Effect of Fluorination and Hydrogen Bonding

Abstract: The solvation of glycine in two ionic liquids (ILs), namely, 1-butyl-3-methylimidazolium acetate, [C(1)C(4)Im][OAc], and 1-butyl-3-methylimidazolium trifluoroacetate, [C(1)C(4)Im][TFA], was studied by a combination of experimental and theoretical methods. The solubility of glycine in both ILs was determined at 333.15 K to be (8.1±0.5) and (1.0±0.5) wt % in [C(1)C(4)Im][OAc] and [C(1)C(4)Im][TFA], respectively. By IR spectroscopy it was found that, when dissolved in the ILs, glycine was mainly present in its zw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…To date, the majority of these solutions have focused on Li + solvation in AILs, motivated by interest in Li + batteries . Other papers have characterized the speciation of alkali metal and alkaline earth ions, , f-block compounds, , biomolecules (amino acids, peptides, or proteins ), or Ru 2+ dyes aimed at nuclear fuel processing, biopreservation, or organic photovoltaics, respectively. The results show that small, charged solutes completely dissociate in the bulk with the solute ions embedded in the polar domains of the IL nanostructure.…”
Section: The Bulk Structure Of Ionic Liquidsmentioning
confidence: 99%
“…To date, the majority of these solutions have focused on Li + solvation in AILs, motivated by interest in Li + batteries . Other papers have characterized the speciation of alkali metal and alkaline earth ions, , f-block compounds, , biomolecules (amino acids, peptides, or proteins ), or Ru 2+ dyes aimed at nuclear fuel processing, biopreservation, or organic photovoltaics, respectively. The results show that small, charged solutes completely dissociate in the bulk with the solute ions embedded in the polar domains of the IL nanostructure.…”
Section: The Bulk Structure Of Ionic Liquidsmentioning
confidence: 99%
“…101 BmimTfA, which is an IL whose anion has very high electron donor ability 46,102 present a strong and almost symmetric band at 1689 cm À1 , which is attributed to asymmetric carboxylate stretching vibration. [103][104][105] The interaction of bmimTfA with solvents was studied in the past and the results showed that also affects this vibration mode. 102,105 For example, the n asym COO À values showed shifts to low wavenumbers upon addition of water (or methanol) to pure bmimTfA, 102,105 general understanding that carboxylate group is a good proton acceptor, the shifting was explained considering H-bonding interaction between water and TfA À .…”
Section: ) Ft-ir Experimentsmentioning
confidence: 99%
“…[16,17] Many interesting features of ILs can be alteredb yt heir functionalization. [21][22][23][24][25] Previously,w ei nvestigated fluorinated aprotic ionic liquids( FAILs) from classical molecular dynamics (MD) simulations, [26] for which we showedt hat nanosegregation is enhanced upon fluorination, but beside the effect of the size or the character of the side chain, the nature and size of the aniona lso influence the microheterogeneous structure. [19] Amongst the several possibilities, fluorination was also examined, [20] which resulted in fluorinated ionic liquids.…”
Section: Introductionmentioning
confidence: 99%